2004
DOI: 10.2134/agronj2004.1523
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tillage on Root Systems of Winter Wheat

Abstract: inducing a higher RLD in the topmost layer under NT (Gregory, 1994;Cannell and Hawes, 1994). There is relatively little information about root growth responseInformation about the impact of tillage on the root under different tillage systems in cool temperate regions. In a 5-yr growth of small-grain cereals is scarce. The root growth field trial at two sites [loamy silt (1995)(1996)(1997)(1998)(1999) and sandy loam soils of winter wheat was similar at later growth stages under (1996-2000)] in the Swiss midland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
53
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(63 citation statements)
references
References 40 publications
6
53
1
1
Order By: Relevance
“…However, among row positions, the maximum RMD was observed along than across the row. The present results of a higher RMD closer to the row were also reported in earlier studies (Liedgens & Richner, 2001;Qin et al, 2004;Qin et al, 2006). There were few roots below 50 cm depth.…”
Section: Discussionsupporting
confidence: 92%
“…However, among row positions, the maximum RMD was observed along than across the row. The present results of a higher RMD closer to the row were also reported in earlier studies (Liedgens & Richner, 2001;Qin et al, 2004;Qin et al, 2006). There were few roots below 50 cm depth.…”
Section: Discussionsupporting
confidence: 92%
“…Dry pea had a larger root diameter, which averaged 0.24 mm. For either crop, no treatment difference in root diameter was observed [LSD (0.05) 00.01 and P 00.05 for wheat, LSD (0.05) 00.02 and P 00.52 for canola and LSD (0.05) 00.03 and P 00.30 for dry pea], which was consistent with reports by Munˇoz-Romero et al (2010) and Qin et al (2004).…”
supporting
confidence: 89%
“…Using partial accounting of CO 2 sources and sinks, Liebig et al [63], however, did not found significant difference in net GWP between alternate-year fallow and continuous cropping in North Dakota. Perennial crops can reduce net GWP and GHGI compared with annual crops [7,44,50] due to higher root biomass production [64,65] and increased soil carbon sequestration [55]. Because land under perennial crops is not tilled and perennial crops are not applied with fertilizers, herbicides, and pesticides, GHG emissions are usually lower with perennial than annual crops [4].…”
Section: Climate Resilient Agriculture -Strategies and Perspectives 92mentioning
confidence: 99%